Novas concepções em transmutadores isotópicos - Wagner Leite Araujo (2014)
The present thesis addresses the concept of Isotope-Transmuter Fuser Cells, which consist of unitary systems capable of managing the main electromagnetic and nuclear processes for the isotope transmutation. The technology consist of inducing fusion reactions between hydrogen isotopes by means of compact accelerators that generate neutrons, which are moderated and conﬁned at the transmutation site. The report begins in the neutron generator technology approach, followed by plasma concepts and assessment of electromagnetic ﬁelds in the plasma. Thereafter, a voltage multiplier is investigated,asaresultacircuitwasdesignedandsimulatedforfeedingtheaccelerators reported in this thesis. Then, the design of an accelerator based on multiple beams is modeled by applying semi-empirical data used to optimize the deuteron current. This accelerator was simulated in a three-dimensional architecture, which showed the behavior of the electric ﬁeld in the accelerator head, as well as the trajectory of the beams in energy proﬁles, providing a deuteron current of about 200 mA on target. Hence, the parameters obtained from electromagnetic simulations led to nuclear calculations and simulations that modeled a unidirectional neutron generator with a shielding system, describing a yield in the order of 1012 neutrons per second. Finally, four models of Transmutation Cells are presented, showing its main components and features. Cells were simulated in electromagnetic and nuclear codes. The results showed yields in the order of 1013 neutrons per second. These levels inside the Cells enable its applications, based on various radionuclide transmutations studied and reported in this work.